2018
DOI: 10.1016/j.scitotenv.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in soil become sensitive to drought under intensive grazing

Abstract: Increasing climatic and anthropogenic pressures on soil ecosystems are expected to create a global patchwork of disturbance scenarios. Some regions will be strongly impacted by climate change, others by agricultural intensification, and others by both. Soil microbial communities are integral components of terrestrial ecosystems, but their responses to multiple perturbations are poorly understood. Here, we exposed soils from sustainably- or intensively-managed grasslands in an agro-silvo-pastoral oak woodland t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 73 publications
2
17
0
1
Order By: Relevance
“…Both anthropogenic and natural factors affect the microbial communities in permafrost. Soil temperature, moisture, organic matter content and pH can influence the microbial community by directly regulating its physiological activities [ 4 , 5 ], while vegetation characteristics [ 5 ], spatiotemporal conversion [ 6 ], grazing intensity [ 7 ] and fertilizer management indirectly impact microbial communities by influencing nutrients in the soil [ 8 ]. Studies have shown that bacterial community structures vary among different habitats and months at small spatial scales due to changes in environmental conditions and ecological interactions [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both anthropogenic and natural factors affect the microbial communities in permafrost. Soil temperature, moisture, organic matter content and pH can influence the microbial community by directly regulating its physiological activities [ 4 , 5 ], while vegetation characteristics [ 5 ], spatiotemporal conversion [ 6 ], grazing intensity [ 7 ] and fertilizer management indirectly impact microbial communities by influencing nutrients in the soil [ 8 ]. Studies have shown that bacterial community structures vary among different habitats and months at small spatial scales due to changes in environmental conditions and ecological interactions [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…bacteria, copiotrophs, drought, extracellular enzyme, fungi, oligotrophs, PLFA, resilience Managed grasslands are very common in agricultural landscapes (Lemaire et al, 2005), such as permanent grassland or sown grasslands included in crop rotation, with large variability of management intensity. Few studies have assessed the effect of grassland management on soil microbial community resilience (Cole et al, 2019;Jurburg, Natal-da-Luz, et al, 2017;Karlowsky, Augusti, Ingrisch, Hasibeder, et al, 2018), and it is still not clear how conventional and ecological systems might differ in their resilience capacity. Here, we used a cross-country experiment (France, Switzerland and Portugal; Figure S1) with intact monoliths brought to a common environment to test how contrasting management (conventional vs. ecological) affects soil microbial properties and their resistance and recovery to different altered rain regimes (dry, wet and intermittent wet/dry as compared to a control 'normal' level).…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial model ecosystems (TME) [31] were used to assess soil salinization effects on soil communities and their potential recovery. These reproducible and controlled semi-field set-ups are accepted tools to evaluate the effects of soil contaminants and other stressors (including climate changes), as well as management practices, on soil communities [32][33][34][35][36][37]. Indeed, they consist of intact soil cores, containing the natural communities of soil fauna and flora, where long-term stability of the soil system is provided, allowing evaluation of not only the effects but also the communities' recovery potential [32,38].…”
Section: Methodsmentioning
confidence: 99%